2017
DOI: 10.1590/s1806-37562016000000033
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of fatigue using the Identity-Consequence Fatigue Scale in patients with lung cancer

Abstract: Objective:To evaluate the properties of the Identity-Consequence Fatigue Scale (ICFS) in patients with lung cancer (LC), assessing the intensity of fatigue and associated factors. Methods:This was a cross-sectional study involving LC patients, treated at a teaching hospital in Brazil, who completed the ICFS. Patients with chronic heart disease (CHD) and healthy controls, matched for age and gender, also completed the scale. Initially, a Brazilian Portuguese-language version of the ICFS was administered to 50 L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
(38 reference statements)
1
1
0
1
Order By: Relevance
“…19 Nowicki et al found that patients with lung cancer had a moderate level of general fatigue in their study; Nogueira et al reported high levels of fatigue in their study. 18,20 Our results are similar to those in the literature. Patients should be informed about how to use energy-saving techniques in managing their fatigue, and the use of Erythropoiesis-stimulating agents (ESA) may be recommended in anemic patients.…”
Section: Discussionsupporting
confidence: 91%
“…19 Nowicki et al found that patients with lung cancer had a moderate level of general fatigue in their study; Nogueira et al reported high levels of fatigue in their study. 18,20 Our results are similar to those in the literature. Patients should be informed about how to use energy-saving techniques in managing their fatigue, and the use of Erythropoiesis-stimulating agents (ESA) may be recommended in anemic patients.…”
Section: Discussionsupporting
confidence: 91%
“…In a study with similar methodology, Nogueira, Araújo, Morano, Cavalcante, Bruin and Paddison [34] assessed intra and interrater reliability. When applying their instrument, they divided actions into two moments: V1 ( rst visit), and V2 (second visit, one week later), using the same statistical analysis as this study.…”
Section: Discussionmentioning
confidence: 99%
“…Os autores responsáveis pelo desenvolvimento desta escala referem que o ICFS possui uma estrutura clara e estável que oferece uma avaliação mais abrangente de fadiga em relação a outros instrumentos que avaliam a fadiga pós-cirúrgica (43) . Foi utilizado para avaliar a fadiga em pacientes com DAC, mas apenas recententemente foi validado para uso no Brasil (44) .…”
Section: As Escalas Dutch Fatigue Scale (Dufs) E a Dutch Exertion Fatunclassified